Structure–Activity Relationship Studies on 6, 7‐Dimethoxy‐2‐phenethyl‐1, 2, 3, 4‐tetrahydroisoquinoline Derivatives as Multidrug Resistance Reversers. (30th June 2017) - Teodori, Elisabetta; Dei, Silvia; Bartolucci, Gianluca; Perrone, Maria Grazia; Manetti, Dina; Romanelli, Maria Novella; Contino, Marialessandra; Colabufo, Nicola Antonio
Abstract: A series of derivatives were synthesized and studied with the aim to investigate the structure–activity relationships of the two P‐glycoprotein (P‐gp) modulators elacridar and tariquidar. Then, different aryl‐substituted amides were inserted, and to explore the effects of varying the amide function, the corresponding isosteric ester derivatives and some alkylamine analogues were synthesized. The new compounds were studied to evaluate their P‐gp interaction profile and selectivity toward the two other ABC transporters, multidrug‐resistance‐associated protein‐1 (MRP‐1) and breast cancer resistance protein (BCRP). Investigation of the chemical stability of the amide and ester derivatives toward spontaneous or enzymatic hydrolysis showed that these compounds were stable in phosphate‐buffered saline and human plasma. This study allowed us to evaluate the selectivity of the three series on the three efflux pumps and to propose the structural requirements that define the P‐gp interaction profile. We identified two P‐gp substrates, a P‐gp inhibitor, and three ester derivatives that were active on BCRP, which opens a new scenario in the development of ligands active toward this pump. Abstract : Resistance is futile : A set of 6, 7‐dimethoxy‐2‐phenethyl‐1, 2, 3, 4‐tetrahydroisoquinoline derivatives were designed and synthesized to develop potent and selective multidrug resistance (MDR) reversing agents. Their behavior on the three ABC transporters, P‐gp, MRP1, and BCRP, was investigated. The results allow us to propose the structural requirements for defining P‐gp selectivity and mechanism of interaction.